PENGARUH HARGA, IKLAN DAN PROMOSI PENJUALAN TERHADAP MINAT BELI KONSUMEN PADA E-COMMERCE LAZADA (Studi Kasus Pada Mahasiswa Jurusan Manajemen Fakultas Ekonomi dan Bisnis UNISMA) - Mohammad Wildan; Rois Arifin; M Hufron (E-JRM : Elektronik Jurnal Riset Manajemen, 2018)
ABSTRACT            This study aims to determine and analyze the influence of prices, advertisements and sales promotions simultaneously and partially on consumer buying interest in Lazada E-Commerce. The method used is purposive sampling technique which is the technique of determining the sample with consideration of certain criteria. The analytical technique used is quantitative descriptive using a Likert scale, multiple linear regression analysis, coefficient of determination and also through f test and  t test using the SPSS program.Based on the results of data analysis simultaneously shows that the influence of price variables, advertising and sales promotion has a significant influence on consumer buying interest in Lazada E-Commerce. While partially the price and advertising variables have no significant effect on consumer buying interest. And for sales promotion variables have a significant influence on buying interest in Lazada E-Commerce. Keywords: Price, advertising, sales promotion, buying interest